The influence of Korean wave and mental health on career selection with self concept as a mediating variable on students in Jakarta - Meryani Meryani; Ruland Willy Jack Sumampouw (Jurnal Riset Manajemen dan Bisnis, 2024)
This study aims to determine the effect of korean wave and mental health on career choice with self concept as a mediating variable in students in Jakarta. The approach in this study is quantitative, with primary data types. The sampling technique used purposive sampling and obtained 100 students who met the criteria with a student population in Jakarta aged 17-25 years and over. This study uses SEM PLS 3 software. The results showed that the korean wave was significant to self concept, mental health had a significant effect on self concept, mental health was found to affect self concept, mental health affected self concept, in addition the Korean wave affected career choice. Interestingly, the korean wave does not directly affect career choice but significantly affects career choice through self concept, and also mental health does not directly affect career choice but significantly affects career choice through self concept.